Developing Item Analysis of Teacher–Made Test for Summative Assessment of Seventh Grade of SMPN 8 Komodo in Academic Year 2020/2021 - Aloysia Moto; Lailatul Musyarofah; Kani Sulam Taufik (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
It was the goal of this study to improve the analysis of teacher-made English test items and to evaluate their quality. The researchers used the Research & Development (R&D) procedure to adapt the ADDIE model. @Aloytemsis, the development's product, became the answer as a result of a needs assessment. At SMPN 8 Komodo, the validity, reliability, index difficulty, and discriminating power of the summative test items were all graded. 43 students who had to take the summative test participated in the field testing. In case of validity, it indicated that 15 items (37.5%) were classified into ‘invalid’ due to the validity index were < 0.279. Meanwhile, 25 items (62.5%) were classified into ‘valid’ criteria regarding the value of validity index were > 0.279. Then, the items under consideration received a reliability index of 0.762. In other words, the “teacher-made English summative test items” were deemed “Good Reliable”. It was discovered that the tough category contained 22 items (55%), the medium category contained 18 items (45%), and the easy category contained just 0 items (0%). Lastly, it is found that the items test were 13 items (32.5%) were in the category ‘Poor’ items due to its value of discrimination index 0.00-0.19. Then, in the category ‘Enough’, there were 12 items (30%). On the other hand, there were 15 items (37.5%) were classified into ‘Good’ items. Unfortunately, there was no items into category ‘Very Good’ items.